Green Hydrothermal Synthesis of Fluorescent 2, 3‐Diarylquinoxalines and Large‐Scale Computational Comparison to Existing Alternatives. Issue 8 (26th March 2021) - Amaya‐García, Fabián; Caldera, Michael; Koren, Anna; Kubicek, Stefan; Menche, Jörg; Unterlass, Miriam M.
Abstract: Here, the hydrothermal synthesis (HTS) of 2, 3‐diarylquinoxalines from 1, 2‐diketones and o ‐phenylendiamines ( o ‐PDAs) was achieved. The synthesis is simple, fast, and generates high yields, without requiring any organic solvents, strong acids or toxic catalysts. Reaction times down to <10 min without decrease in yield could be achieved through adding acetic acid as promoter, even for highly apolar biquinoxalines (yield >90 % in all cases). Moreover, it was shown that HTS has high compatibility: (i) hydrochlorides, a standard commercial form of amines, could be used directly as combined amine source and acidic catalyst, and (ii) Boc‐diprotected o ‐PDA could be directly employed as substrate that underwent HT deprotection. A systematic large‐scale computational comparison of all reported syntheses of the presented quinoxalines from the same starting compounds showed that this method is more environmentally friendly and less toxic than all existing methods and revealed generic synthetic routes for improving reaction yields. Finally, the application of the synthesized compounds as fluorescent dyes for cell staining was explored. Abstract : In hot water : 2, 3‐Diarylquinoxalines and biquinoxalines are synthesized in a rapid, efficient and green fashion in nothing but high‐temperature water. Through a large‐scale computational analysis, the herein reported reaction conditions are compared with all reported syntheses of the presented compounds.